Pengaruh Dimensi Staffing terhadap Insiden Keselamatan Pasien berdasarkan Agency For Healthcare Research And Quality (AHRQ) Di RSU Haji Surabaya - Setya Budi Rahayu (Universitas Airlangga, 2017)
The incidence of patient safety is an indicator that can be used to describe the quality of hospital services. Based on data obtained from reports IKP in RSU Haji Surabaya in 2015 is known to have occurred 40 patient safety incidents. This research to analyze the influence of staffing dimension base on AHRQ with patient safety incidents in service work unit RSU Haji Surabayausing simple linier regression test. The results showed from the 38 unit service work RSU Haji Surabaya there are 18 units (47,36%) categorized as a strong staffing dimension with a positive response ≥ 75%, 16 units (42,11%) the medium categorized staffing dimension with a positive response from 75% - 50% and 4 units (10,53%) the weak categorized staffing dimension with a positive response < 50%. And according to a report IKP RSU Haji Surabaya January - October 2016 there were 22 incidents of patient safety that consists of 5 KTD, 3 KNC and 14 KTC. In this research can be concluded that there is no significant relationship between staffing dimension with patient safety incidents in service work unit RSU Haji Surabaya. This can be due to by various factors that occurs in the system.Keywords: AHRQ, Patient Safety Incident, Staffing Dimension